2019
DOI: 10.1111/tmi.13289
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of tuberculosis and its socioeconomic influencing factors in mainland China 2013–2016

Abstract: Background To assess the spatial epidemic characteristics of TB and identify the key areas for disease prevention and control. Objective To explore the spatial distribution and socioeconomic influencing factors of TB in mainland China from 2013 to 2016. Methods Spatial autocorrelation was used to explore the spatial distribution characteristics of TB at the quantitative level. Ordinary least squares (OLS) and geographically weighted regression (GWR) models were conducted to explore the association between fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…In the present study, we also found that the number of doctors was strongly related to the COVID-19 risk in typical labor export provinces. Similar to our work, studies by Wang and Du showed that the abundance of medical resources and level of medical accessibility in a region play a vital role in the prevention of infectious diseases [ 33 , 34 ]. Therefore, improving the abundance of medical resources and level of medical accessibility in a region is an effective measure to prevent and control the local spread of infectious diseases.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we also found that the number of doctors was strongly related to the COVID-19 risk in typical labor export provinces. Similar to our work, studies by Wang and Du showed that the abundance of medical resources and level of medical accessibility in a region play a vital role in the prevention of infectious diseases [ 33 , 34 ]. Therefore, improving the abundance of medical resources and level of medical accessibility in a region is an effective measure to prevent and control the local spread of infectious diseases.…”
Section: Discussionsupporting
confidence: 86%
“…Studies from China and Ethiopia also reported that low access to health care services was associated with increased number of TB cases. [26,33].…”
Section: Plos Onementioning
confidence: 99%
“…Per capita GDP can provide insights into the effect of in macro-level economic determinants and the effects of policy on spatio-temporal variations in elderly TB incidence. Previous studies indicated that per capita GDP was significantly associated with TB incidence at the country or provincial level [ 12 , 33 35 ]. A country with a high level of per capita GDP can allocate greater financial resources to TB control.…”
Section: Discussionmentioning
confidence: 99%
“…Based on current evidence, income, education, occupation and population density account for most health inequalities within countries [ 11 15 ]. Furthermore, unbalanced regional development, with resulting consequences for socio-economic conditions, plays an important role in the incidence of TB [ 12 ].…”
Section: Introductionmentioning
confidence: 99%